Five-Finger Hypnosis Therapy as a Holistic Nursing Approach to Blood Pressure Control in Hypertensive Patients in Anjir Serapat Muara 1 Village - Navisa, Zahwa; Milasari, Milasari; Chintami, Yulia; Wahdini, Wahdini; Rusady, Fara Della (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Hypertension is a long-term non-communicable condition influenced by both physiological and psychological factors, highlighting the need for complementary non-pharmacological interventions in blood pressure management. Five-finger hypnosis therapy is a relaxation technique that can be utilized in nursing care as an intervention for managing blood pressure. This community service activity was conducted to implement five-finger hypnosis therapy as part of a holistic nursing approach for residents with hypertension in Anjir Serapat Muara 1 Village. A total of 33 respondents participated in health education sessions, guided five-finger hypnosis practice, and blood pressure measurements conducted before and after the intervention. The findings indicated that 84.8% of respondents exhibited a decrease in systolic blood pressure, whereas 39.4% demonstrated a reduction in diastolic blood pressure. The mean systolic blood pressure decreased from 151 mmHg to 138 mmHg, and the mean diastolic blood pressure decreased from 95 mmHg to 91 mmHg.